EXPERIMENTAL INVESTIGATIONS OF TOOL WEAR IN VIBRATION-ASSISTED TURNING OF INCONEL 718 - Dodla S. (My University, 2025)
In the current paper, the effect of tool wear for a constant period of time (360 s) during conventional and ultrasonic assisted machining of Inconel 718 is investigated in terms of cutting forces, temperature, and deviation measurements. For fixed process parameters turning experiments have been performed with and without the application of tangential vibration. Ultrasonic assisted turning (UAT) experiments have been compared with conventional turning (CT). The experimental results reveal that cutting forces and temperature increase linearly in the case of UAT whereas remaining constant in CT for a constant period of time. Besides the tool wear rate in the case of UAT is more than that in the CT. © 2022. The Author(s).